Balance Scorecard Analysis to Measure Hospital Performance - Thahan, Andreas Ferik Fiada; Noch, Muhammad Yamin; Suratini, Suratini (The Journal of Business and Management Research, 2024)
This study aims to evaluate and analyze the performance of Provita Hospital using the Balanced Scorecard approach. The population of this study includes all patients—general, BPJS, and insurance—who received treatment or care at Provita Hospital Jayapura in 2022. A sample of 90 patients was selected. The data analysis method used is mediation analysis with data processed using SmartPls version 3.00 software. The findings indicate that the performance of Provita Hospital is generally reasonable. This is evidenced by results from the financial, customer, and internal business processes and growth and learning perspectives, all of which exceed standard hospital benchmarks. Specifically, the hospital shows strong liquidity, solvency, and cost recovery rate performance, although improvements are needed in the total assets turnover ratio. Customer retention rates are high, but customer acquisition rates need enhancement. Internal processes, measured by LOS and GDR, meet the standards, but BOR requires attention. Employee satisfaction and training are satisfactory, although retention is slightly above the ideal rate. The study highlights the importance of continuous improvement in financial management, customer service, and employee development. The results suggest practical strategies for hospital management to enhance overall performance by leveraging strengths and addressing weaknesses identified in the Balanced Scorecard analysis. These findings are valuable for policymakers and hospital administrators aiming to improve healthcare service quality and operational efficiency.